Tidal responses of the semi-enclosed Bohai Sea to the long-term expansion of the Yellow River Delta - Jiayue Sun; Man Zhang; Jianjun Zhou (Frontiers in Marine Science)
River deltas, formed by fluvial sediment accumulation, act as dynamic interfaces between land and sea. The Yellow River Delta (YRD) has prograded rapidly into the semi-enclosed shallow Bohai Sea (BS) over the past century. While tidal dynamics are recognized as key drivers of estuarine morphology and ecology, it is unclear how and to what extent this deltaic expansion impacts the tidal regime in the BS. This study investigates the tidal responses of the BS to both historical (circa 1855, 1962, 1981, 2003) and projected century-scale delta coastline advancement, utilizing numerical simulations and theoretical analysis. The results indicate that the seaward expansion of the delta alters tidal resonance patterns, inducing tidal responses in a nonlinear way across the BS. Specifically, historical delta expansion enhanced tidal flux and currents monotonically across major bays in the BS, whereas future sedimentation over the coming decades leads to an overall reduction in tidal dynamics. Locally, tidal currents and sediment transport capacity are expected to increase around the active lobe owing to river mouth protrusion at the expense of having the river base level raised; they decrease near the abandoned lobes with standby river courses, potentially hindering sediment dispersal and threatening the delta’s morphological stability. Furthermore, the basin-scale tidal weakening caused by the delta expansion may diminish water exchange capacity in the BS, posing challenges for ecological environment and economic services.